DF-8: a specific scale for assessing work fatigue in professional drivers. Issue 3 (3rd July 2022) - Tàpia-Caballero, Patricia; Serrano-Fernández, María-José; Boada-Grau, Joan; Boada-Cuerva, Maria; Araya-Castillo, Luis; Vigil-Colet, Andreu
Abstract : The study objective is to create a scale specifically for measuring driver fatigue and to analyze the scale's psychometric properties. The participants were 518 Spanish drivers. We carried out an exploratory factor analysis (EFA) and the first subsample obtained a single-item solution (eight items). We then performed a confirmatory factor analysis (CFA) with a second subsample. The results were root mean square error of approximation (rmsea) = 0.05, comparative fit index (CFI) = 0.94 and Tucker–Lewis index (TLI) = 0.92, which corroborates the previous results and maintains the same number of elements. The resulting dimension shows good reliability. The scale scores were then related to several external correlates and other scales, and showed good convergence and criteria validity. The results indicate that the scale for assessing work fatigue specifically in professional drivers – driver fatigue (DF-8) – is a reliable and valid instrument.